Cellular membrane cholesterol is required for porcine reproductive and respiratory syndrome virus entry and release in MARC-145 cells - Ying Sun; ShaoBo Xiao; Dang Wang; Rui Luo; Bin Li; HuanChun Chen; LiuRong Fang (Science China Life Sciences, 2011)

Comparison of initial hydrolysis of the three dimethyl phthalate esters (DMPEs) by a basidiomycetous yeast, Trichosporon DMI-5-1, from coastal sediment - Zhu-Hua Luo; Yi-Rui Wu; Ka-Lai Pang; Ji-Dong Gu; Lilian L. P. Vrijmoed (Environmental Science and Pollution Research, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Warming and grazing affect soil labile carbon and nitrogen pools differently in an alpine meadow of the Qinghai–Tibet Plateau in China - Yichao Rui; Shiping Wang; Zhihong Xu; Yanfen Wang; Chengrong Chen; Xiaoqi Zhou; Xiaoming Kang; Shunbao Lu; Yigang Hu; Qiaoyan Lin; Caiyun Luo (Journal of Soils and Sediments, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

Foot-and-mouth disease virus leader proteinase inhibits dsRNA-induced RANTES transcription in PK-15 cells - Dang Wang; Liurong Fang; Jing Bi; Quangang Chen; Lu Cao; Rui Luo; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

Activation of NF-κB by nucleocapsid protein of the porcine reproductive and respiratory syndrome virus - Rui Luo; Liurong Fang; Yunbo Jiang; Hui Jin; Yanwei Wang; Dang Wang; Huanchun Chen; Shaobo Xiao (Virus Genes, 2011)